Xylopia aromatica: initial growth and nutritional status of seedlings in degraded soil conditioned with residues (Research, Society and Development, 2022)
The revegetation of degraded areas, with edaphic compromise and absence of vegetation, needs to be preceded by actions that improve the edaphic characteristics and thus provide conditions for the full development of crops. The species Xylopia aromatica, popularly known as pimenta-de-macaco, occurs in the Cerrado and has been used in the revegetation of degraded areas. Thus, the objective of this research was to evaluate the initial growth and nutritional status of X. aromatica seedlings introduced in an area under reclamation, conditioned with aquatic macrophytes (RO) and sugarcane bagasse ash (RA), and compare them to seedlings of the same species found in preserved Cerrado (CER). The study was conducted in an area where the vegetation and the superficial soil horizons (horizons A and B) were suppressed. In the experimental area, the residues RO and RA were added at different doses. Seedlings of 10 cerrado tree species were introduced into the area, among them X. aromatica. One year after, their nutritional status was evaluated. The seedlings in the recovering area showed leaf contents similar to those of the CER seedlings for K, Ca, Mg, B, and Mn, and higher for Cu, Fe, and Zn. The soil of the experimental area showed similarities to the soil of the CER, but still requires adjustments in the levels of P and organic matter. The growth of X. aromatica showed better response in the treatment with 32 t ha-1 of macrophytes and 30 t ha-1 of ash, doses indicated to obtain the best results.